Education and training for preventing sharps injuries and splash exposures in healthcare workers - Cheetham, Shelley; Thompson, S.; Liira, J.; Afilaka, O.; Liira, H. (John Wiley & Sons, Ltd., 2016)
© 2016 The Cochrane Collaboration. Published by John Wiley & Sons, Ltd. This is the protocol for a review and there is no abstract. The objectives are as follows: To assess the effects of education and training interventions versus no intervention or alternative interventions for preventing sharps injuries and splash exposures in healthcare workers.